Legal Certainty of Jurisdiction and Authority of the International Criminal Court (ICC) Regarding the Detention of Rodrigo Duterte in the “War on Drugs” Case - Kaloko, Ilhamda Fattah; Harmelia; Putra, Rian Rusmana (Universitas Medan Area, 2025)
This article aims to analyze the relationship between state withdrawal and the jurisdiction of the International Criminal Court (ICC), particularly in the context of the Philippines' decision to withdraw from the Rome Statute. The problem is focused on the legal implications of such a withdrawal, especially in terms of how it influences the ICC's authority to investigate and prosecute crimes committed prior to the effective withdrawal date. This issue is exemplified by the Philippines' controversial